Fenofaza brstenja kot pokazatelj podnebnih značilnosti pokrajine - Prah, Klemen (Geografski obzornik, 2003)
The climatic characteristics of a region can be indirectly established by observing the vegetation. One of the methods is to observe the phenological stage of budding of a certain plant species on different heights above sea level. The article presents the developement of phenological stages of budding of beech and vine, the sort of Welsh Riesling (Vitis vinifera cv. laški rizling), on the south slopes of the Boč mountain. Determined were measuring posts where the developement of buds was regulary observed and, concurrently, air temperature was also measured and weather characteristics recorded.
Keywords: brstenje; drevesa; fenofaze; fenologija; fenološki razvoj; klima; klimatologija